A Review of Technology Acceptance Model Application in User Acceptance of Autonomous Vehicles - Ho, Jen Sim; Tan, Booi Chen; Lau, Teck Chai; Pang, Suk Min (JOIV : International Journal on Informatics Visualization, 2025)
Touting the merits of reducing traffic fatalities by eliminating human errors and promoting social benefits, autonomous vehicle technology has been rapidly developed over the last few decades. Using the systematic review approach, this study provides an overview of current studies that apply the Technology Acceptance Model (TAM) in shaping user acceptance of autonomous vehicles. Based on a set of inclusion and exclusion criteria, a total of 16 articles out of 792,364 articles were retained for further analysis. The factors that have garnered the most attention from researchers are the technical and psychological factors, with the most frequent constructs integrated in these studies being perceived ease of use, followed by perceived usefulness, trust, attitude, perceived enjoyment, and perceived innovativeness. This study presents three key findings. The first shows that 36 potential antecedents influencing AV adoption were incorporated into TAM. Excluding the baseline model antecedents, the most studied factors were trust, personal innovativeness, and perceived enjoyment. Trust is widely recognized as a crucial factor in AV adoption and requires longitudinal research, as it is a dynamic element that evolves. The second finding concerns the various causal relationships between the constructs. The results showed mixed outcomes, which may be due to differences in levels of automation examined, geographical contexts, and socio-demographic factors. Third, the gaps identified in Section 4 can guide policymakers, researchers, and automakers in developing effective future strategies and research directions. Ultimately, a deeper understanding of public acceptance can facilitate the safe deployment of AVs on roads, leading to benefits such as improved traffic safety and increased sustainability for society and the economy.